2023
DOI: 10.1002/dad2.12418
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of informal care time, distress, depression, and quality of life in care partners along the trajectory of Alzheimer's disease

Abstract: Introduction We evaluated determinants associated with care partner outcomes along the Alzheimer's disease (AD) stages. Methods We included n = 270 care partners of amyloid‐positive patients in the pre‐dementia and dementia stages of AD. Using linear regression analysis, we examined determinants of four care partner outcomes: informal care time, caregiver distress, depression, and quality of life (QoL). Results More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 71 publications
1
0
0
Order By: Relevance
“…On the other hand, overload was negatively correlated with the level of attention and quality of life, similar to the findings of Canadians Mank et al 21 , which demonstrated that caregiver partners, who spent more time on care, had greater burden and worse quality of life since the onset of the disease. This may result from the high demand for care, which limits free time for self-care, social interaction and leisure.…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, overload was negatively correlated with the level of attention and quality of life, similar to the findings of Canadians Mank et al 21 , which demonstrated that caregiver partners, who spent more time on care, had greater burden and worse quality of life since the onset of the disease. This may result from the high demand for care, which limits free time for self-care, social interaction and leisure.…”
Section: Discussionsupporting
confidence: 86%